2003
DOI: 10.1086/345904
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Resistance inStreptococcus pyogenes

Abstract: Streptococcus pyogenes isolated from blood and urine samples obtained from a 78-year-old woman was tested for susceptibility, and fluoroquinolone resistance (minimum inhibitory concentration of levofloxacin, 16 microg/mL) was found. DNA amplification and sequencing revealed a serine81-->tyrosine substitution in gyrA and 2 substitutions in parC: serine79-->phenylalanine and alanine121-->valine. This is the second report of a clinical isolate of S. pyogenes with high-level fluoroquinolone resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Using this cut-off for screening clinical isolates, as many as 14 mutations have been described in the QRDRs of parC, parE, gyrA and gyrB [4,[7][8][9][10]12,[14][15][16]29] and 4 new mutations were encountered in the present study. The QRDR sequence comparison M a n u s c r i p t of susceptible and non-susceptible isolates of the same emm types revealed that the S79F in parC is a relevant mutation for ciprofloxacin non-susceptibility.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Using this cut-off for screening clinical isolates, as many as 14 mutations have been described in the QRDRs of parC, parE, gyrA and gyrB [4,[7][8][9][10]12,[14][15][16]29] and 4 new mutations were encountered in the present study. The QRDR sequence comparison M a n u s c r i p t of susceptible and non-susceptible isolates of the same emm types revealed that the S79F in parC is a relevant mutation for ciprofloxacin non-susceptibility.…”
Section: Discussionmentioning
confidence: 73%
“…The first description of a GAS clinical isolate resistant to ciprofloxacin [minimal inhibitory concentration (MIC) >32 mg/L) was reported in 2000 [7]. So far, seven cases of highly resistant strains have been described [7][8][9][10][11]. At the same time, GAS with reduced susceptibility to FQs have been increasingly reported worldwide [4,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Our data from pediatric isolates of S. pyogenes confirmed this M/emm 6 predominance finding. However, it is interesting to note that although M/emm 6 isolates have intrinsic fluoroquinolone resistance, the highly resistant isolates reported in the literature have been M/ emm types 2, 12, and 89 rather than M/emm type 6 (Yan et al, 2000b;Reinert etal., 2004;Richter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in naturally arising resistant isolates of S. pyogenes occur in the QRDR of gyrA at Ser-81 with or without replacement at Met-99 and in the QRDR of parC at Ser-79 with or without change at Ala-121 (Yan et al, 2000b;Richter et al, 2003;Yan et al, 2000a;Alonso et al, 2002). The point mutation patterns among the pediatric isolates are similar to those previously documented in adult isolates and somewhat similar to those key residue replacements in S. pneumoniae but with much less variety of amino acid substitutions (Boos et al, 2001;Janoir et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation